2007
DOI: 10.1063/1.2429058
|View full text |Cite
|
Sign up to set email alerts
|

A thermochemically competitive local hybrid functional without gradient corrections

Abstract: Following the suggestion of local hybrid functionals with position-dependent exact-exchange admixture [J. Jaramillo, G. E. Scuseria, and M. Ernzerhof, J. Chem. Phys. 118, 1068 (2003)], a functional that mixes only local and exact exchange plus local correlation has been constructed. With a simple local mixing function for the position dependence, this Lh-SVWN functional provides atomization energies for the G2-1 set that are competitive with currently available state-of-the-art functionals like, e.g., B3LYP. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
170
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 131 publications
(170 citation statements)
references
References 33 publications
0
170
0
Order By: Relevance
“…As for the 'pig2' CF above, we may thus choose one of these three terms for partitioning and treatment according to eqn (12). Taking, e.g., the second term of eqn (37) without prefactor and partitioning it as…”
Section: B98-based ''Meta-gga'' Calibration Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the 'pig2' CF above, we may thus choose one of these three terms for partitioning and treatment according to eqn (12). Taking, e.g., the second term of eqn (37) without prefactor and partitioning it as…”
Section: B98-based ''Meta-gga'' Calibration Functionmentioning
confidence: 99%
“…We will apply integration by parts to them in the same way as done above for the original energy density (14). That is, we (i) apply a partitioning (11), thus (ii) building (when possible) a new CF according to eqn (12) and (18).…”
Section: Second-and Higher-order Gga Calibration Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, its thermochemical performance is rather poor. 14 Later, Kaupp and co-workers 16,17,20 showed that parametrized mixing functions including…”
Section: ͑1͒mentioning
confidence: 99%
“…Most subsequent thermochemical tests of local hybrids have been performed non-self-consistently. 16,17,[19][20][21]23 In this work, we present self-consistent GKS calculations using the screened and LC local hybrid functionals defined in Eqs. ͑10͒ and ͑11͒.…”
Section: ͑14͒mentioning
confidence: 99%